ACCELERATION OF THE ABILITY TO READ THE QURAN THROUGH THE QURANI SIDOGIRI METHOD - Magfiroh, Laili Nadifatil (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The Al-Qur’an is an immunization for every Muslim's spirituality. Reading it will turn anxiety into calm. Currently, practical and fast methods of learning the Qur'an are developing with various advantages. Among these methods is the Sidogiri Qurani Method (MQS). The Sidogiri Qurani Method (MQS) is a method for reading the Qur'an created by the Sidogiri Islamic Boarding School. This research aims to describe the implementation of accelerated reading of the Koran through the Qurani Sidogiri method at MI Zainul Anwar and its effect on students. In this research, the type of approach used is a qualitative approach. The data collection technique in this research is by observing and interviewing. The type of research used is field research (case study). The results of implementing the Sidogiri Quranic method at MI Zainul Anwar are by the desired targets and expectations, namely making it easier and faster to learn to read the Koran properly and correctly. This can be seen from observations made during the learning process and students' persistence in participating in learning and increasing student achievement shown by good daily grades